Prognostic value of LDH and α-HBDH dynamic levels for 1-year overall survival and progression-free survival in patients with extensive-stage small-cell lung cancer treated with chemoimmunotherapy - Li, Wanjing; Du, Guochang; Lu, Shuangqing; Zhu, Hui; Zhao, Ke; Yu, Jinming; Yang, Yanqin (Frontiers in Oncology, 2026)
BackgroundExtensive-stage small cell lung cancer (ES-SCLC) remains a lethal malignancy with limited prognostic biomarkers. This study evaluated the prognostic utility of lactate dehydrogenase (LDH) and α-hydroxybutyrate dehydrogenase (α-HBDH) levels at baseline and after 2 cycles of treatment in ES-SCLC patients receiving first-line chemoimmunotherapy.MethodsContinuous variables were converted into categorical ones based on optimal cutoffs identified by ROC curve analysis (maximizing Youden’s index). Overall survival (OS) and progression-free survival (PFS) were calculated via the Kaplan–Meier method and compared via the log-rank test. In addition, the Cox regression model was used to analyze prognostic factors. Associations between LDH and α-HBDH levels and clinical parameters (T/N stage, age, and immune-related toxicity) were analyzed using the Mann–Whitney U test and binary logistic regression.ResultsA cohort of 201 ES-SCLC patients treated with chemotherapy and immune checkpoint inhibitors was analyzed retrospectively. Elevated baseline serum LDH >245 U/L and α-HBDH >182 U/L levels predicted poor OS (p = 0.046, HR = 1.798, 95% CI: 1.020–3.167; p = 0.007, HR = 2.268, 95% CI: 1.288–3.994); inadequate 2-cycle reductions (ΔLDH ≤ 108.5U/L; Δα-HBDH ≤ 62.5U/L) further predicted poor OS (p<0.001, HR = 2.561, 95% CI: 1.291–5.080; p<0.001, HR = 2.807, 95% CI: 1.457–5.411). For progression-free survival, no significant difference was observed between patients with elevated baseline serum LDH >245 U/L or α-HBDH >182 U/L and those with normal levels; similarly, there was no significant difference between patients with an on-treatment increase (ΔLDH>12.5 U/L or Δα-HBDH>0.5 U/L from baseline) and those with a lesser increase or decrease. (P = 0.768, HR = 1.055, 95% CI: 0.739–1.507 for baseline LDH; P = 0.529, HR = 1.121, 95% CI: 0.785–1.601 for baseline α-HBDH; P = 0.115, HR = 0.719, 95% CI: 0.457–1.131 for ΔLDH; P = 0.094, HR = 0.730, 95% CI: 0.494–1.080 for Δα-HBDH). Advanced T4/N3 stage and age ≥65 years significantly modulated biomarker trajectories (p<0.05).ConclusionLDH and α-HBDH serve as key prognostic biomarkers in ES-SCLC patients undergoing first-line chemoimmunotherapy. We established clinically validated thresholds, which can guide treatment by identifying patients with elevated or insufficiently declining levels as high-risk, thereby supporting early and targeted therapeutic intervention.